[George Soros in Vienna]
CEP event at the House of Industry in Vienna, Austria. George Soros is a panelist in a discussion on the disintegration of the Soviet Union. The other panelists are: Alojz Peterle (Former Prime Minister and Minister of Foreign Affairs in Slovenia), Gerhard Bruckman (University Professor in Vienna), Hannes Swoboda (Austrian politician), and Hans Magenschab (Austrian journalist).